Аpplication macrolides at demodecosis of dogs - Решетило, О. І.; Нікіфорова, О. В. (Scientific Progress & Innovations, 2016)
Demodecosis is a common disease among dogs in central and adjoining microdistricts of city Sumy. Over the past three years there was a decrease in the number of detected cases of dogs’ demodecosis. The animals under 1 years old have been ailing more frequent – 67,85 %, at the age from 1 to 4 years – 22,62 %, and the amount of incidence of ailing dogs at the age from 4 to 10 years and elder 10 years were 6,0 % and 3,57 % respectively. Demodecosis have been detected in 22 breeds of dogs. Outbred dogs were ailing more frequent, the rate was 15,47 %, Pug dogs – 14,29 % and German shepherd – 10,71 %. EE «Advocate» drug was – 90 % and «Dectomax» and «Ivermectin 1 %» – 80 %.